IMPROVING CRITICAL THINKING SKILLS OF FUTURE FOREIGN LANGUAGE TEACHERS IN THE DIGITAL EDUCATIONAL ENVIRONMENT: DIAGNOSTICS, CRITERIA, AND EXPERIMENTAL RESULTS - o‘g‘li, Ismoiljonov Shuxratjon Boymirza (Research Focus International Scientific Journal, 2026)
This article presents the methodology, results, and scientific-practical conclusions of a large-scale experimental study conducted to improve the critical thinking skills of future foreign language teachers in a digital educational environment. The CTDF (Critical Thinking Development Framework) model was tested in a quasi-experimental study involving 463 students from 6 higher education institutions of the Republic of Uzbekistan. The results showed that the students in the experimental group demonstrated a statistically significant increase in critical thinking skills across all five criteria (p < 0.001; Cohen d = 1.47–1.68).